How to translate clinical trial results into gain in healthy life expectancy for individual patients. (30th March 2016) - Dorresteijn, Jannick A N; Kaasenbrood, Lotte; Cook, Nancy R; van Kruijsdijk, Rob C M; van der Graaf, Yolanda; Visseren, Frank L J; Ridker, Paul M
Abstract : Treatment effects from randomised trials are typically expressed as numbers needed to treat to prevent one adverse disease event during a fixed time interval (eg, five or 10 years). In the actual patient, however, many diseases are chronically progressive, despite treatment. Examples are diabetic nephropathy, some types of malignancies, osteoporosis, and atherosclerosis. In these examples, the aim of treatment is not to prevent but to delay the occurrence of symptomatic disease. Thus the actual effect of treatment is gain in disease-free life expectancy